PERSEPSI MASYARAKAT TERHADAP PERAN RT-RW DALAM MITIGASI BENCANA RAWAN BANJIR DI WILAYAH TAMARUNANG INDAH 1 KABUPATEN GOWA - Sri Mawar; Rusdi; Ibrahim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
His study aims to analyze: 1) Description of RT-RW contribute mitigation efforts the Tamarunang Indah 1 Area Gowa Regency. 2) factors influencing community perceptions of RT-RW in mitigation. And 3) Community perceptions of RT-RW in mitigation. Research employed descriptive qualitative method. data collection methods included observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and accurate findings. The research findings reveavaled the following: indicate that: 1) The description RT-RW is reflected through their involvement in coordinating community service activities for cleaning drainage channels, monitoring environmental conditions during periods of high rainfall, and delivering information to residents through direct communication as well as neighborhood group media. 2) Community perceptions are influenced by experiences in facing floods, communication between RT-RW and residents, and community’s preparedness in responding to potential flooding. 3) public perception of the role of RT-RW in flood disaster mitigation shows that RT-RW is seen as a party that understands local conditions, is aware of flood-prone areas, and is involved in monitoring and mobilizing flood prevention efforts. These findings illustrate the involment of TR-RW and community perceptions in flood risk management at the neighborhood level.